Assessment and mechanism analysis of municipal solid waste incineration bottom ash as aggregate in cement stabilized macadam. (20th January 2020) - Yan, Kezhen; Sun, Hao; Gao, Fengqian; Ge, Dongdong; You, Lingyun
Abstract: The objective of the paper is to assess the feasibility of using solid waste incineration (MSWI) bottom ash (BA) as cement-stabilized macadam (CSM) aggregate. CSM was prepared by replacing natural limestone aggregate with MSWI BA in different proportions (0%, 5%, 10%, 20%, and 30%). The physical properties, chemical properties, and micro-morphology of MSWI BA were studied to explore the mechanism of MSWI BA aggregate in CSM. The mechanical properties (unconfined compressive strength, cleavage strength, compressive resilience modulus), drying shrinkage, freezing resistance, and leaching behavior of CSM were tested. The results showed that MSWI BA had low density, low strength, high water absorption, high porosity, hydraulicity, and cementitious activity. Substitution of MSWI BA for natural limestone reduced the unconfined compressive strength, the cleavage strength, and the compression modulus of resilience of CSM, but these parameters still met the requirements of the specification. The CSM containing MSWI BA had higher cumulative water loss rate and smaller average dry shrinkage coefficient than traditional CSM. Adding 0–20% MSWI BA reduced the cumulative dry shrinkage strain of CSM. The residual strength ratio of CSM increased slightly at first and then decreased rapidly, and the CSM containing 0–30% MSWI BA met the freezing resistance requirements of semi-rigid base materials. The leaching concentration of heavy metals of CSM curing 7 days with 30% MSWI BA was still far below the limit of Chinese standard GB 5085.3.